Analisis perbedaan kinerja perusahaan dan kinerja modal intelektual di Indonesia - Lewi Sugianto; Hendra Wijaya (Journal of Business & Banking, 2020)
Business development is needed to increase its competitive advantage. In business development, the companies can do a business combination through mergers and acquisitions. Mergers and acquisitions are expected to improve intellectual capital performance. Apart from improving the performance of the company, it is also expected to increase their company performance. This study aims to examine and analyze difference in intellectual capital performance and company performance 1 year before and 1-4 years after mergers and acquisitions. The objects in this study are all companies listed on the Indonesia Stock Exchange and do mergers and acquisitions in 2011-2014. The data analysis technique used is the Wilcoxon test. The results of this study found that mergers and acquisitions made the performance of intellectual capital and company performance decline. This is because when a company merges and admits, the management who manages cannot directly use the intellectual capital they have, but must study it in order to be able to use it. Therefore, it takes time to be able to synergize it so that the performance of intellectual capital will be better. The deteriorating performance of intellectual capital shows the added value that can be created by the company to make profits worse, which will make the company's performance also decreased.